LSD1: Expanding Functions in Stem Cells and Differentiation - Carlos Martinez-Gamero (MDPI AG, 2021)
Embryonic stem cells (ESCs) and induced pluripotent stem cells (iPSC) provide a powerful model system to uncover fundamental mechanisms that control cellular identity during mammalian development. Histone methylation governs gene expression programs that play a key role in the regulation of the balance between self-renewal and differentiation of ESCs. Lysine-specific demethylase 1 (LSD1, also known as KDM1A), the first identified histone lysine demethylase, demethylates H3K4me1/2 and H3K9me1/2 at target loci in a context-dependent manner. Moreover, it has also been shown to demethylate non-histone substrates playing a central role in the regulation of numerous cellular processes. In this review, we summarize current knowledge about LSD1 and the molecular mechanism by which LSD1 influences the stem cells state, including the regulatory circuitry underlying self-renewal and pluripotency.